2017
DOI: 10.1051/0004-6361/201630027
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation for He-like ions withZ= 20–42

Abstract: Aims. Spectral lines of He-like ions are among the most prominent features in X-ray spectra from a large variety of astrophysical and high-temperature fusion plasmas. A reliable plasma modeling and interpretation of the spectra require a large amount of accurate atomic data related to various physical processes. In this paper, we focus on the electron-impact excitation (EIE) process. Methods. We adopted the independent process and isolated resonances approximation using distorted waves (IPIRDW). Resonant stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 89 publications
(114 reference statements)
1
23
1
Order By: Relevance
“…Combined with our earlier results [2][3][4][5][6][7][8]18], along with those of Si et al [9] and Li et al [10], the present work completes data for all F-like ions with Z ≤ 74. These works include a larger number of levels than generally available in the literature, are comparatively more accurate, and hence can be confidently and reliably applied in the diagnostics and modelling of a variety of plasmas, including astrophysical and fusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Combined with our earlier results [2][3][4][5][6][7][8]18], along with those of Si et al [9] and Li et al [10], the present work completes data for all F-like ions with Z ≤ 74. These works include a larger number of levels than generally available in the literature, are comparatively more accurate, and hence can be confidently and reliably applied in the diagnostics and modelling of a variety of plasmas, including astrophysical and fusion.…”
Section: Discussionsupporting
confidence: 89%
“…For example, during the past one decade in a series of papers [2][3][4][5][6][7][8], we have reported energy levels, radiative rates (A-values), oscillator strengths (f-values), line strengths (S-values), and lifetimes (τ ) for F-like ions with 36 ≤ Z ≤ 74. Similarly, Si et al [9] and Li et al [10] have reported data for ions with 24 ≤ Z ≤ 30 and 31 ≤ Z ≤ 35, respectively. Since their data are of comparable high accuracy there is no (real) need to revisit these ions.…”
Section: Introductionmentioning
confidence: 87%
“…As was emphasized earlier [1], almost all working codes are under continuous process of development and improvements, and the errors (as and when detected) are corrected. Similarly, there is always scope for improvement over any calculation, either by improving the accuracy of the wavefunctions and/or enlarging the size by inclusion of additional levels, and this has recently been demonstrated by Si et al [75,76] for He-like ions and by Benda and Houfek [77] for atomic hydrogen.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…The Atomic Database project (AtomDB) has evolved from the Raymond-Smith code (Raymond & Smith 1977) to the current AtomDB website, database, and models. The goal of the project is to accurately model the emission from an optically thin, collisionally ionized plasma, particularly on emission in the X-ray and extended UV wavebands.…”
Section: Atomic Database Project and Astrophysical Plasma Emission Codementioning
confidence: 99%
“…Such differences in what should be a relatively simple, robust diagnostic raise questions about how to best F I G U R E 1 Comparison of diagnostic G ratios calculated using electron collision strength data from three sources: blue crosses (Whiteford et al 2001), orange circles (Aggarwal & Keenan 2013), and green triangles (Si et al 2017). The Aggarwal dataset truncates at lower temperature than the others, so is only shown at lower temperatures evaluate new data, or identify where and when data accuracy requires improvement.…”
Section: Database Access: Apedmentioning
confidence: 99%